The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/1878-0261.12574
|View full text |Cite
|
Sign up to set email alerts
|

Prospective detection of mutations in cerebrospinal fluid, pleural effusion, and ascites of advanced cancer patients to guide treatment decisions

Abstract: Many advanced cases of cancer show central nervous system, pleural, or peritoneal involvement. In this study, we prospectively analyzed if cerebrospinal fluid (CSF), pleural effusion (PE), and/or ascites (ASC) can be used to detect driver mutations and guide treatment decisions. We collected 42 CSF, PE, and ASC samples from advanced non‐small‐cell lung cancer and melanoma patients. Cell‐free DNA (cfDNA) was purified and driver mutations analyzed and quantified by PNA‐Q‐PCR or next‐generation sequencing. All 42… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 41 publications
(52 reference statements)
3
52
0
Order By: Relevance
“…The prior reports showed that there was discordance in EGFR mutation status between primary tumor and CSF (35). It may result from low cellularity or ctDNA in the small amount of CSF or the low concentrations of the first and second generation of EGFR TKIs in CSF inadequate to drive the occurrence of T790M (36).…”
Section: Discussionmentioning
confidence: 99%
“…The prior reports showed that there was discordance in EGFR mutation status between primary tumor and CSF (35). It may result from low cellularity or ctDNA in the small amount of CSF or the low concentrations of the first and second generation of EGFR TKIs in CSF inadequate to drive the occurrence of T790M (36).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, other body fluids have been evaluated as an alternative source of tumor derived DNA. In fact, cfDNA from fluids in sites adjacent to metastases such as cerebrospinal fluid, pleural effusion, and ascites was found at higher levels, resulting in a more effective method in for detecting relevant mutations [50].…”
Section: Circulating Cell-free Dnamentioning
confidence: 99%
“…One of the alternate, more readily accessible liquid biopsy sources that has been exploited for molecular profiling is ctDNA obtained from serous body cavity effusion fluids. 30,46 A large percentage of patients with advanced stage NSCLC initially present with a malignant pleural effusion that may be the only tissue source for diagnosis and biomarker testing. Recent studies evaluating the cellfree component of these samples for tumor mutational profiling have highlighted the role of centrifuged supernatant fluids from these effusion samples in providing clinically relevant genomic information for primary driver mutations as well as those in a resistance setting.…”
Section: Pleural Effusion and Ascitic Fluidmentioning
confidence: 99%